MitraClip implantation followed by insertion of a left ventricular assist device in patients with advanced heart failure - Kreußer, Michael; Hamed, Sonja; Weber, Andreas; Schmack, Bastian; Volz, Martin J.; Geis, Nicolas; Grossekettler, Leonie; Pleger, Sven Torsten; Ruhparwar, Arjang; Katus, Hugo; Raake, Philip (ESC heart failure, 2020)
Aims Mitral valve regurgitation (MR) is common in patients with advanced heart failure (HF). Percutaneous mitral valve repair (PMVR) via MitraClip (MC) has emerged as a feasible treatment strategy for these high-risk patients. However, as HF often further progresses, there is a frequent need for left ventricular assist device (LVAD) implantation in these patients. We aimed to investigate whether prior MC implantation affects the subsequent LVAD implantation and outcome. Methods and results Thirty-seven patients with advanced HF and significant MR who underwent LVAD implantation were retrospectively analysed. Follow-up data were collected at 1 year after LVAD implantation. Primary endpoint was all-cause mortality. Secondary endpoint included peri-operative parameters and clinical development depicted as New York Heart Association (NYHA) class and Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) level. Seventeen patients initially received a MC device (MC group), resulting in a significant reduction in MR grade. After MC, NYHA class and INTERMACS level further worsened, leading to subsequent LVAD implantation after a median time of 475 days in the MC group. At LVAD implantation, overall characteristics were comparable with those of the patients undergoing LVAD implantation without prior MC placement (no-MC group). Procedural data revealed a higher incidence of right ventricular (RV) failure needing mechanical RV assistance and a longer need for nitric oxide ventilation in the MC group after LVAD implantation. One-year survival was slightly better in the no-MC group compared with the MC group [41% (n = 7/17) vs. 65% (n = 13/20); P = 0.15], albeit event-free survival was comparable between both groups, MC and no-MC. Conclusions LVAD implantation after MC is feasible and safe. However, in patients with advanced HF and severe MR, PMVR may only delay a needed LVAD implantation and thereby lead to poorer peri-operative RV function and impaired outcome. Arguably, these patients might benefit from the timely management of advanced HF by the means of early LVAD implantation or heart transplantation.